THE CONTRIBUTION OF ISLAMIC CAPITAL MARKET AND ISLAMIC INSURANCE TO INCLUSIVE ECONOMIC DEVELOPMENT IN INDONESIA - Rani Puspitaningrum; Nabila Hermina (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The study aims to identify the contribution of some Islamic financial instruments from Islamic capital markets and Islamic non-bank financial institutions to inclusive economic development in Indonesia. While some studies have examined the contribution of some Islamic financial instruments to a single measure of economic indicators, this study tries to fill the gap in the context of multi indicators to explain economic development, so the authors propose an inclusive economic development index that consists of 21 indicators. This study employed a quantitative research method using secondary data from 2011-2020 from several sources (Financial Service Authority, the Ministry of Finance Republic Indonesia, and the Ministry of National Development Planning (BAPPENAS)). The main variables used are the Jakarta Islamic Index (JII) market capitalization, total outstanding Sukuk, Islamic insurance total claim, and inclusive economic development index. The research data is analyzed using multiple regression linear models. The result found that only the total outstanding Sukuk significantly impacted inclusive economic development. In contrast, the others variables are insignificant.